An Analysis of Slang Words on TikTok by Gen Z - Jaya, Saskia Chaerunnisa; Alamsyah, Alamsyah; Max, Jonathan Irene Sartika Dewi (Fakultas Ilmu Budaya Universitas Mulawarman, 2025)
In order to interact and exchange conversation with Gen Z we need to fully understand their language. The constant flow of trends on the internet affected the development of language and slang. With the rate which language changes it also means that it is easily forgotten. This research served as an inventory for newly invented slang words by Gen Z on TikTok. This research main objective analyzed the type and function of slang words that are used by Gen Z on the infamous social media platform TikTok. This research applied Allan and Burridge's theory of slang type and function that are used on the TikTok platform by Gen Z from October to December of 2023. This research employed qualitative research as the methodology with a sociolinguistics approach. The analysis involved in this research are data condensation, coding process, and meaning interpretation. The analysis revealed that there are occurrences of fresh and creative, flippant, imitative, acronym, and clipping, with occurrences of the function to address, to humiliate, and to express impression. Based on the analysis, the most dominant slang type is imitative with to address as the most used slang function on the TikTok platform. It could be concluded that, Gen Z tends to reuse an already existing vocabulary and used them to address a situation or activity.